Certified by nature: a new species of the gelatinous alga Dudresnaya (Dumontiaceae, Rhodophyta) from the Azores - Gabriel, Daniela (2021)
ABSTACT: Dudresnaya, a red algal genus belonging in the family Dumontiaceae, currently comprises 21 species of gelatinous algae from tropical to subtropical waters worldwide. Dudresnaya verticillata and D. crassa have been reported for the Azorean islands in species checklists since 1992 and 2001, respectively. The present work is the first taxonomic study of representatives of the genus in this archipelago. The Azorean specimens previously identified as Dudresnaya verticillata are here recognized as a new species based on four molecular markers (nuclear LSU, mitochondrial COI, and plastid rbcL and UPA). Genetic differences between the new taxon and its closest related species are: COI – 9,81%; rbcL – 7,35%; UPA – 3,44%; and LSU – 1,04%. The morphological and reproductive diagnostic features of the new species are described. Gametophytes are dioecious. Male plants present abundant spermatia borne on the outer cortical cells. Female plants bear 3-4 celled carpogonial branches and auxiliary cell branches borne at the base of cortical branches close to the axial filaments. Carposporophytes comprise numerous carpospores, forcing the surrounding cortical filaments to spread apart as they grow. Tetrasporophytes were not observed. Relationships among species of Dudresnaya are explored.